Effects of the AfCFTA for German and European companies - Julian Hinz; Sonali Chowdhry; Anna Jacobs; Rainer Thiele (Kiel Institut für Weltwirtschaft (IfW Kiel), 2022)
In May 2019, the African Continental Free Trade Area (AfCFTA) agreement entered into force. In numerous respects, the AfCFTA can be considered a historic milestone towards trade liberalization on the African continent. Following ten rounds of official negotiations beginning in June 2015, the agreement now spans 55 African Union Member States of which 43 have already deposited their instruments of ratification. By connecting these economies, AfCFTA has become the largest trading bloc in the world in terms of market size, covering more than 1.3 billion consumers with combined GDP of USD 2.5 trillion. The AfCFTA's core objective is to deepen the economic integration of the African continent by creating a single market for the movement of goods, services, capital and natural persons. In this study, we assess the status quo of trade within AfCFTA economies and between AfCFTA and EU economies, and outline three hypothetical future outcomes of AfCFTA for different levels of trade liberalization. The study was conducted with the support of Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ) GmbH on behalf of the Federal Ministry for Economic Cooperation and Development (BMZ).
Additional information: Kiel Institute Study - durch das Kiel Institut für Weltwirtschaft (IfW Kiel)
Keywords: 330